Factors Influencing the Uptake and Sustainable Use of Soil and Water Conservation Measures in Bubaare Micro-Catchment, Kabale District, South Western Uganda - Willbroad, Byamukama; Ssemakula, E; Kalibwani, R (OMMEGA PUBLISHERS, 2019)
Soil erosion and declining soil productivity still continue to manifest in most of the agricultural systems found in Sub-Sahara Africa. As a consequence, this has threatened the agricultural productivity, biodiversity, water quality and availability as well as the livelihoods of the poor who depend on land. In Uganda, this has been attributed to poor land use practices with inadequate SWC measures and persistent nutrient mining of the soils with little or no replenishment. Highland areas of Kabale are reported to be severely affected by soil erosion and declining soil fertility despite continued efforts by farmers to conserve soil and water resources. The study examined the Soil and Water Conservation measures in Bubaare micro-catchment. The study was conducted to assess factors (i) physical (ii) institutional and (iii) socio-economic influencing adoption and sustainable use of soil and water conservation measures in Bubaare micro- catchment in Kabale district. The study was cross sectional in nature employing both qualitative and quantitative approaches to capture data from a sample of 397 respondents using semi-structured questionnaires interviews and observation. Data was analyzed using SPSS version 16 to generate both descriptive and inferential statistics that aided in presentation and interpretation. It was found that 22.9% of the farmers in the area were conserving soil and water using mulches and cover crops, 21.9% agroforestry, 16.8% terraces, 11.3% surface drainage ways, 8% contour bunds, 8% grass bunds, 11% trenches/ditches and 3.3% woodlots. Factors that were statistically determined to significantly influence the adoption and sustainable use of soil and water conservation implementation in Bubaare micro-catchment were physical, institutional, and socio-economic factors. In this regard, several key recommendations were made which involved extending financial services to the farmers, communication and information access, training and experience sharing, strengthening research and development, education and awareness, providing technical and financial support.